How digital mindfulness training promotes meaning in life among social workers: a parallel mediation analysis and latent profile analysis - Rui, Chang; Cao, Jun; Tan, Fuqiang (Frontiers in Psychiatry, 2025)
IntroductionThis study investigates the mechanisms by which digital mindfulness training promotes meaning in life among social workers and explores individual heterogeneity in this process.MethodsA parallel mediation model was used to test the pathways from digital mindfulness training to meaning in life. Latent Profile Analysis (LPA) was employed to identify distinct subgroups among the participants.ResultsAll five proposed hypotheses received strong empirical support. Our analysis revealed that social workers who participated in digital mindfulness programs reported a stronger meaning in life. The parallel mediation model identified two distinct pathways: digital mindfulness training was associated with (1) reduced perceived social exclusion and, separately, (2) fewer psychotic-like experiences. Both of these factors, in turn, independently contributed to a greater meaning in life. The LPA identified five distinct subgroups: the "Flourishing Professional," "Socially Isolated yet Resilient," "Typical Practitioner," "Internally Struggling but Connected," and "High-Risk and Distressed." These groups differed significantly in meaning in life, with the "High-Risk and Distressed" category scoring the lowest.DiscussionViewed together, these patterns form a coherent explanatory structure that helps clarify how mindfulness interventions may operate. The findings also point to the importance of tailoring program content and delivery to address the particular vulnerabilities and strengths of each subgroup, rather than relying on a single, generic format.